2017
DOI: 10.1111/medu.13302
|View full text |Cite
|
Sign up to set email alerts
|

Cultural minority students’ experiences with intercultural competency in medical education

Abstract: As cultural minority students were confronted with microaggressions, the medical school did not succeed in creating a safe education environment for all students. Contrary to their aims and intentions, intercultural competence activities had limited effect and seemed to support the polarisation of cultural minority and majority students and teachers. This can be seen as pointing towards a hidden curriculum privileging majority over minority students. For structural integration of intercultural competency in me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 40 publications
2
27
0
Order By: Relevance
“…The presence and everyday experiences of minority students and doctors, increasing the diversity of caregivers has been a crucial topic in international literature since the 1990s (1)(2)(3)(4). These studies show that minority students and medical professionals are disadvantaged in several areas or experience discrimination starting from the admission procedure (1,2,5), through experiencing explicit or implicit day-by-day rejection during the training (6)(7)(8)(9) or the questioning of medical competences (6, 10, 11) up until the lack of role models or mentors (8,10,12).…”
Section: Background On Minority Medical Studentsmentioning
confidence: 99%
See 3 more Smart Citations
“…The presence and everyday experiences of minority students and doctors, increasing the diversity of caregivers has been a crucial topic in international literature since the 1990s (1)(2)(3)(4). These studies show that minority students and medical professionals are disadvantaged in several areas or experience discrimination starting from the admission procedure (1,2,5), through experiencing explicit or implicit day-by-day rejection during the training (6)(7)(8)(9) or the questioning of medical competences (6, 10, 11) up until the lack of role models or mentors (8,10,12).…”
Section: Background On Minority Medical Studentsmentioning
confidence: 99%
“…Several studies highlight the signi cance of mentors or 'role models' in the personal development of medical students -especially in the case of minority students (8,9,12,18,21,34,35). Regarding cultural competences, belonging to a minority community could be an advantage for caregivers: the knowledge of habits, language and problems help them better understand and reassure their patients, and it could present an opportunity for shaping the knowledge and attitude of colleagues (9,10,36).…”
Section: Minority Doctors and Multicultural Medicinementioning
confidence: 99%
See 2 more Smart Citations
“…In this issue of Medical Education , Leyerzapf and Abma present a qualitative evaluation of cultural minority students’ experiences with cultural competency teaching at a Dutch medical school . Using interviews, observations and a focus group with a broad and diverse population of students, the authors identified several challenges that confront minority students in the context of cultural competency teaching.…”
mentioning
confidence: 99%